2015
DOI: 10.1002/jms.3642
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phase I and II metabolites of the new designer drug α‐pyrrolidinohexiophenone (α‐PHP) in human urine by liquid chromatography quadrupole time‐of‐flight mass spectrometry (LC‐QTOF‐MS)

Abstract: Pyrrolidinophenones represent one emerging class of newly encountered drugs of abuse, also known as 'new psychoactive substances', with stimulating psychoactive effects. In this work, we report on the detection of the new designer drug α-pyrrolidinohexiophenone (α-PHP) and its phase I and II metabolites in a human urine sample of a drug abuser. Determination and structural elucidation of these metabolites have been achieved by liquid chromatography electrospray ionisation quadrupole time-of-flight mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 32 publications
4
32
0
Order By: Relevance
“…32 Dihydro metabolites formed by reduction of the alpha-keto group detected in PHH incubations 11,15,16,18 could not be found in the pS9 incubations, which is consistent with results reported in previous studies. 32 Dihydro metabolites formed by reduction of the alpha-keto group detected in PHH incubations 11,15,16,18 could not be found in the pS9 incubations, which is consistent with results reported in previous studies.…”
Section: In Vitro Metabolism Using Ps9supporting
confidence: 91%
See 2 more Smart Citations
“…32 Dihydro metabolites formed by reduction of the alpha-keto group detected in PHH incubations 11,15,16,18 could not be found in the pS9 incubations, which is consistent with results reported in previous studies. 32 Dihydro metabolites formed by reduction of the alpha-keto group detected in PHH incubations 11,15,16,18 could not be found in the pS9 incubations, which is consistent with results reported in previous studies.…”
Section: In Vitro Metabolism Using Ps9supporting
confidence: 91%
“…This is in accordance to Richter et al, comparing different in vitro models for 4-methoxy-alpha-pyrrolidinovalerophenone. 16 At least all results from in vitro models should be confirmed by authentic human urine. This is in accordance with urine findings for alpha-PHP and alpha-PVT.…”
Section: Comparison Of Different Modelsmentioning
confidence: 96%
See 1 more Smart Citation
“…The relative percent abundance for VLZ and each metabolite (M1–M12) formed in urine, faeces and plasma are summarized in Figures a–c. As the metabolism studies were conducted without any reference standards, there may be uncertainty regarding the estimation of metabolites and therefore ion counts have been utilized to carry out semi‐quantitative estimation of metabolites . Based on the present study, it was observed that VLZ was found in all in vivo samples and in comparatively higher percent in faeces (13.93%).…”
Section: Resultsmentioning
confidence: 62%
“…So comprehensive study of biotransformation pathways and the knowledge of the possible toxicity of metabolites are prerequisite for the drug discovery and development . Over the years, liquid chromatography–electrospray ionization tandem mass spectrometry (LC–ESI/MS/MS) in combination with accurate mass measurements has been widely used for the identification and characterization of metabolites …”
Section: Introductionmentioning
confidence: 99%